Abstract 1122‐000180: Contrast‐Enhanced Transcranial Doppler Ultrasonography Versus Transesophageal Echocardiography as Screening Tool in Embolic Stroke - Fourcand, Farrah; Gadallah, Nancy; Ghori, Arifa; Torres, Danisette; Panezai, Spozhmy; Suhan, Laura; Mehta, Siddhart; Kirmani, Jawad (Stroke: vascular and interventional neurology, 2021)
Abstract only Introduction : Right‐to‐left (RtL) intracardiac and intrapulmonary shunts are associated with embolic stroke. Although contrast‐enhanced transcranial doppler ultrasonography (ceTCD) and transesophageal echocardiography (TEE) are used in embolic stroke work up, there are no standardized guidelines as to which test should be considered as ‘gold standard’. Our objective is to evaluate the sensitivity of contrast‐enhanced TCD and TEE in detecting right‐to‐left shunt to determine respective utilities as screening tools. Methods : Electronic medical records of subjects presenting with acute neurological symptoms who had ceTCD and TEE were evaluated. Sensitivity and specificity were calculated. Based on the respective prevalence of intracardiac and intrapulmonary shunts, positive predictive value, negative predictive value, and test accuracy were determined for ceTCD and TEE. Social Science Statistics was used for data analysis. Results : From June 2016 to August 2021, of 7,498 ischemic stroke patients, 260 patients were suspected of having strokes related to right to left shunts and underwent ceTCD and TEE for detection of cardioembolic sources for stroke. A positive right‐to‐left shunt was detected in 83 subjects. Detection by ceTCD was confirmed by the operator for 81 patients while 2 were considered false positive results (delayed sporadic High Intensity Transient Signals (HITS)). Sensitivity of ceTCD was 97.65% (95% CI [91.76%, 99.71%]). No safety concerns were identified in patients undergoing ceTCD. Of those with positive ceTCD (68.57%, n = 35) were detected by Valsalva, and all of those 35 patients had negative TEE. TEE had sensitivity of 70.34% (95% CI [61.23%, 78.39%]). Conclusions : Contrast‐enhanced TCD has superior sensitivity, is cost‐effective, practical, and a safe alternative to TEE in identifying intracardiac or intrapulmonary shunts. Screening superiority of ceTCD may lie in ability to elicit shunts during Valsalva maneuvers. To our knowledge this is the largest single center series confirming ceTCD as a gold standard tool for screening of right to left shunts.